Human Rights Interpretation in the Dimension of Pancasila Ideology - Arifin, Ridwan (Law Research Review Quarterly, 2016)
Pancasila as a basic guideline for the state in the context of the rule of law in Indonesia, makes the interpretation of Pancasila itself diverse. However, all government actions and existing legislation must be based on Pancasila values. Likewise with the context of human rights. This paper analyzes and illustrates the interpretation of human rights in the Pancasila dimension. Various interpretations emerge from various cases of upholding and fulfilling human rights in Indonesia, both in the context of national principles and the principles of international law.